3T-32=0

Simple and best practice solution for 3T-32=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3T-32=0 equation:


Simplifying
3T + -32 = 0

Reorder the terms:
-32 + 3T = 0

Solving
-32 + 3T = 0

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + 3T = 0 + 32

Combine like terms: -32 + 32 = 0
0 + 3T = 0 + 32
3T = 0 + 32

Combine like terms: 0 + 32 = 32
3T = 32

Divide each side by '3'.
T = 10.66666667

Simplifying
T = 10.66666667

See similar equations:

| (xD^4+D^3)y=0 | | 4x^4+7x^2-6=0 | | x(x+1)=x^2+5 | | 6(5x-3)=36x | | 5x-(2)=2x+13 | | 1.0t+6.34t-2.12t= | | 4x-13=33 | | -21=k+9 | | c=(-20)+(-8) | | y=x^3+18x^2+77x+60 | | 2x^2+2x+14=0 | | 6.3+4=5.3x | | 5x+11=3x-8 | | Log[4](28)-log[4](28)= | | 2x^2-x-66=0 | | 7-5-3=46 | | 5x-3(2x-1)=25-3x | | x-(x*.05)=450 | | 25x-4=-45x+12 | | 10+(-14)= | | -86=-7x+4(3x-9) | | 10x-18=32+5x | | 4x-2(6x+8)=40 | | 2/3(x-3)=4x+18 | | 6[x-(2-x)]=-4(8x+3) | | 6-10x=27-3x | | 25x-45x=-4+12 | | 535=55x | | -2x+10=-18-6x | | -5+2u=-7 | | 3n+75=50+2n | | -(-7+4x)=8x+18 |

Equations solver categories